2013
DOI: 10.1186/1129-2377-14-79
|View full text |Cite
|
Sign up to set email alerts
|

Headache and comorbidity in children and adolescents

Abstract: Headache is one of the most common neurological symptom reported in childhood and adolescence, leading to high levels of school absences and being associated with several comorbid conditions, particularly in neurological, psychiatric and cardiovascular systems. Neurological and psychiatric disorders, that are associated with migraine, are mainly depression, anxiety disorders, epilepsy and sleep disorders, ADHD and Tourette syndrome. It also has been shown an association with atopic disease and cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 108 publications
5
117
1
4
Order By: Relevance
“…13 Factores de risco ambientais como o consumo de substâncias, traumatismos cranianos, perturbação do padrão de sono e coexistência de enxaqueca, aumentam o risco para o desenvolvimento de crises de cefaleia em salvas. As perturbações do sono, nomeadamente privação do sono ou sono prolongado, podem promover o início de crises de cefaleia, nomeadamente enxaqueca, 21 no entanto o sono pode ser o factor decisivo para a resolução de uma crise de cefaleia. História de abuso na infância tem sido mostrada como factor de risco para esta comorbilidade, assim como uso frequente de corticóides ou abuso de medicação.…”
Section: Mecanismos Subjacentes à Comorbilidadeunclassified
“…13 Factores de risco ambientais como o consumo de substâncias, traumatismos cranianos, perturbação do padrão de sono e coexistência de enxaqueca, aumentam o risco para o desenvolvimento de crises de cefaleia em salvas. As perturbações do sono, nomeadamente privação do sono ou sono prolongado, podem promover o início de crises de cefaleia, nomeadamente enxaqueca, 21 no entanto o sono pode ser o factor decisivo para a resolução de uma crise de cefaleia. História de abuso na infância tem sido mostrada como factor de risco para esta comorbilidade, assim como uso frequente de corticóides ou abuso de medicação.…”
Section: Mecanismos Subjacentes à Comorbilidadeunclassified
“…Relatively little research has been devoted to the group of child and adolescent patients with diseases of the nervous system, in whom there simultaneously appear signs of a spectrum of mental disorders that require treatment. The comorbidity of neurological and psychiatric disorders has been described, among others, in children with headaches [13,14], migraine [15], tic disorder [16], Tourette's syndrome [17], juvenile multiple sclerosis [18] and epilepsy [7,19]. The present work discusses the characteristics of patients from a diagnostic developmental neurology department, who manifested severe signs of mental problems and, as a result, were in need of a psychiatric consultation.…”
Section: Introductionmentioning
confidence: 92%
“…In one study, 29.6% of CDH patients met criteria for at least one current psychiatric diagnosis, and 34.9% met criteria for at least one-lifetime psychiatric diagnosis [53] . Depressive and anxiety disorders being the common disorders, other being dysthymia, phobic disorder, obsessive compulsive disorder, somatoform disorders, sleep difficulties and disorders (insufficient and poorer sleep quality, co-sleeping with parents, anxiety related to sleep, night waking, nightmares, bedwetting and pavor), suicidal ideation and an increased risk of suicidality [30,48,[50][51][52][54][55][56][57][58][59][60][61] .The lifetime prevalence of major depression was threefold higher in persons with migraine and in persons with a severe headache compared with controls [62] .TTH is associated with fewer close friends and had a higher rate of divorced parents [63] . Previous studies have shown a significant negative correlation between total intelligence quotient, verbal intelligence quotient, performance intelligence quotient and the frequency of headache attacks [64] .…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…Previous studies have shown a significant negative correlation between total intelligence quotient, verbal intelligence quotient, performance intelligence quotient and the frequency of headache attacks [64] . Neurological disorders associated with a headache and migraine, are mainly epilepsy, ADHD and Tourette syndrome [52,55,61,65] .The prevalence of epilepsy in patients with migraine varies from 1 to 17%, with an average of 5.9%, and greatly exceeds that of the general population (0.5-1%) [61] . The risk of migraine is more than twice as high in subjects with epilepsy both in probands and in relatives, compared to people without epilepsy [66] .The most obvious association is between migraine with aura (MWA) and epilepsy, with a high prevalence of MWA (30.4%) than other types of primary headache in children with seizures [67] .…”
Section: Co-morbiditiesmentioning
confidence: 99%
See 1 more Smart Citation